Կանանց քաղաքացիավարական ներկայացվածության հիմնախնդիրները ՀՀ-ում - Ալեքսանյան Աշոտ (YSU Journal of International Affairs, 2014)
In this article the main issues of democratization of the political system of Armenia contributes to the realization of the constitutional rights and fundamental freedoms, basic values and interests of the individual and the legalconsolidation of civiliarchic institutions. The article also reveals the necessity of gender social partnership and dialogue in the process of democratization. At the present stage of democratic reform takes center stage analysis of the socio-political status of the Armenian women, as well as a comparative analysis of the legal mechanisms to protect their rights. In this context, particular importance is the formation of an effective strategy to promote gender equality and social harmonization, which may be relevant in the regulation of social and labor relations, with the involvement of trade unions and women’s NGOs. Particular attention is paid to the social dimension of legal activities and social orientation of public organizations is to protect the rights and freedoms of women, thereby contributing to the formation of the welfare state in Armenia. Effective protection of social rights and freedoms of women is an important characteristic of contemporary reality, which has an impact on the democratic integration of the Armenian society at national, European and global level. At this stage of European integration the legal framework for the protection of rights and freedoms of women is gradually formed in Armenia, and legislation complies with international legal standards in the field of gender policy. However, it is necessary that the relevant legal provisions have been implemented to ensure the socio-political development of women and consolidation of civiliarchic mechanisms for gender equality. In the conclusion, based on research by the author is invited to make a number of institutional reforms in Armenia.